PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV UPT SD NEGERI 060938 MEDAN JOHOR - Nurhayati Simanullang, Damaris; Antonius Remigius Abi; Eka Margareta Sinaga; Regina Sipayung; Heka Maya Sari Sembiring (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Think Pair Share learning model on student learning outcomes in Pancasila Education for Grade IV students at the State Elementary School 060938 Medan Johor, 2024/2025 Academic Year. This study used a quantitative method with a pretest-posttest experimental design in one group, involving 30 students as a sample. Data collection was carried out through tests, learning outcomes, and student participation questionnaires, which were tested for validity and reliability. The pretest results showed that the average value of student learning outcomes was 55.33 in the low category, while the posttest results increased to 82.53 in the high category. The correlation test showed a calculated r value of 0.638 and a table r value of 0.361, indicating a strong relationship between the think-pair-share cooperative learning model and student learning outcomes. Furthermore, the results of the hypothesis test using the t-test obtained a calculated r value of 4.386 > 1 table 2.048, indicating a significant influence between the use of the think-pair-share model and student learning outcomes. Therefore, the research hypothesis states that there is a significant influence of the think-pair-share cooperative learning model.